MyHEARTSMAP: development and evaluation of a psychosocial self-assessment tool, for and by youth. Issue 1 (24th July 2019) - Virk, Punit; Laskin, Samara; Gokiert, Rebecca; Richardson, Chris; Newton, Mandi; Stenstrom, Rob; Wright, Bruce; Black, Tyler; Doan, Quynh
Abstract : Background: Paediatric mental health-related visits to the emergency department are rising. However, few tools exist to identify concerns early and connect youth with appropriate mental healthcare. Our objective was to develop a digital youth psychosocial assessment and management tool (MyHEARTSMAP) and evaluate its inter-rater reliability when self-administered by a community-based sample of youth and parents. Methods: We conducted a multiphasic, multimethod study. In phase 1, focus group sessions were used to inform tool development, through an iterative modification process. In phase 2, a cross-sectional study was conducted in two rounds of evaluation, where participants used MyHEARTSMAP to assess 25 fictional cases. Results: MyHEARTSMAP displays good face and content validity, as supported by feedback from phase 1 focus groups with youth and parents (n=38). Among phase 2 participants (n=30), the tool showed moderate to excellent agreement across all psychosocial sections (κ=0.76–0.98). Conclusions: Our findings show that MyHEARTSMAP is an approachable and interpretable psychosocial assessment and management tool that can be reliably applied by a diverse community sample of youth and parents.